Truth and falsehood in Judith: A Greimassian contribution - Hobyane, Risimati S. (HTS teologiese studies, 2016)
Narratives are never meant to be neutral in their rhetorical intent. They have power not onlyto reveal realities and prevail worldviews but also to create new realities and new worldviewsby refuting illusions and falsehood, and affirming the truth. The Judith narrative is a goodexample for the exploration of this claim. This article contributes by employing the thematiclevel of analysis, the veridictory square in particular, of the Greimassian approach to narratives,to map out the possible illusions and affirming the truth within the second temple Judaism.The study of the veridictory square as informed by the level of analysis, mentioned above,seems to persuade the reader by first, extracting the truth from illusion and thereafter exposingand shaming falsehood in Judith. Subsequently, the article asserts that Judith is not neutral in itsintent but was designed to deal with illusive ideas that might have been impacting the wellbeingof the second temple Judaism.